Tension and shear anchorage systems for limestone structures. (22nd February 2021) - Porcarelli, Silvia; Shedde, Devina; Wang, Ziren; Ingham, Jason M.; Giongo, Ivan; Dizhur, Dmytro
Highlights: 54 anchors tested under tension & 24 anchors tested under shear in limestone. Wide 18–22° cone failure zone of influence, compared to 35° or 45° existing models. Anchor shear capacity governed by limestone material properties and anchor diameter. A 12% moisture increase in limestone reduces strength by up to 50%. Concrete capacity models produce load predictions which are conservative by up to 30%. Abstract: Using anchorage systems to improve and repair existing buildings has been a favoured technique for many years. Whilst there has been an abundance of anchor performance analysis associated with anchorage into concrete, there has conversely been a comparative lack of investigation concerning the behavioural response of anchorage systems in low strength materials such as sedimentary stone. In the study reported herein, 78 adhesive anchors were subjected to tensile and shear testing in limestone blocks that were sourced from Oamaru, New Zealand. Three nominal anchor rod diameters (ɸ12, ɸ16, ɸ20 mm) and two different bond agents (two-part epoxy adhesive, cement-based grout) were employed in the test regime. 54 anchors were installed to three varying depths of embedment described as a multiple of the anchor diameter (3ɸ, 5ɸ, 10ɸ), and were subjected to monotonic tension loading, and an additional 24 anchors were installed at one constant depth and subjected to a semi-cyclic shear loading regime. The results of these tension and shear experiments are summarised, with several anchor failure mechanism identified. Under tension, epoxy anchor behaviour was governed by the limestone strength, whereas grout anchor failure was governed by the bond strength. Anchor capacities in shear for epoxy and grout anchors were similar, however displacements were typically larger for grout anchors due to a low elastic modulus of grout. Also included is an investigation of the influence of moisture content on the strength properties of the limestone. In addition, a predictive equation for anchorage capacity within limestone is developed by applying analytical formulations originally conceived for anchorages installed into concrete, in order to study their applicability to weaker natural stone. The study provides a practicable baseline for future testing and the design of anchorage in sedimentary limestone. This dataset could be supplemented in future studies via investigations into alternative loading regimes, and/or the construction of limestone walls to investigate how local wall morphology impacts anchorage performance.